Meningkatkan Keterampilan Komunikasi Siswa melalui Penerapan Experiential Learning - Muh. Asharif Suleman (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
In an increasingly complex and globally connected information era, students' communication skills are an important key to facing challenges and achieving success in the dynamic modern world. The development of technology and social media has changed the way we communicate, speeding up the exchange of information and increasing the importance of effective communication skills. Thus, improving students' communication skills is a top priority in education to prepare them for a connected and dynamic world. This research aims to identify the effectiveness of implementing experiential learning in improving students' communication skills. A qualitative approach with a case study design was used to explore the effectiveness of implementing experiential learning. data collection techniques in the form of in-depth interviews, observation, and document study. The research was conducted in an elementary school in the city of Yogyakarta. The research results show that the experiential learning approach is very effective in improving students' communication skills. With this research, it is hoped that teachers can use experiential learning methods, which can be a new alternative for improving students' communication skills in elementary schools.